The production bioethanol from Ceratophyllum demersum L . in Iraq - AL Zaidi, Dmoua kamil; Husam Mohammed Kredy (University of Thi-Qar Journal of Science, 2023)
Biofuels have attracted a lot of attention due to the growing demand for energy resources and concerns about greenhouse gas emissions. Unlike other green energy resources, biofuels like bioethanol, can provide liquid fuels that is essential for transportation. Second-generation bioethanol can be produced from lignocellulosic biomass through acid hydrolysis and fermentation. Lignocellulosic biomass is widely available and does not affect on the nutritional needs of agricultural crops. In this study, the aquatic plant Ceratophyllum demersum was used. Ceratophyllum demersum is a type of invasive aquatic plant that can live in fresh and brackish waters, and it is abundant in most regions of southern Iraq. The bioethanol with the highest concentration was identified by high-performance liquid chromatography (HPLC). The results showed that 14% of bioethanol was produced in the absence of acid hydrolysis, while the concentration of it increased to 25% with the presence of acid hydrolysis. Acid hydrolysis aims to increase the breaking bonds of lignin and hemicellulose, increase the porosity of the material, and damage the crystalline structure of cellulose, and thus facilitates its conversion to glucose and increases the percentage of ethanol production.